1983
DOI: 10.1901/jaba.1983.16-69
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Child's Self‐evaluation Program on Compliance With Parental Instructions in the Home

Abstract: A self-evaluation program was implemented with a kindergarten-aged boy in the home to increase compliance with parent instructions and decrease inappropriate verbal behavior. The self-evaluation package included the child's assessing the appropriateness of his behavior in 5-min intervals, receiving chips for positive self-evaluations, and exchanging chips for a reward following experimental sessions. In a reversal design, analyses were conducted of the effectiveness of the self-evaluation program, the requisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…As mentioned, self-management is a widely researched treatment technique that utilizes the client as an active participant in the treatment process. These procedures have not only been shown to be effective with normal populations (e.g., Drabman, Spitalnik, & O'Leary, 1973;O'Brien, Riner, & Budd, 1983;Sagotsky, Patterson, & Lepper, 1978), but have also been used successfully with persons evidencing mild to moderate mental retardation (Gardner, Cole, Berry, & Nowinski, 1983;Horner & Brigham, 1979;Shapiro & Klein, 1980;Shapiro, McGonigle, & Ollendick, 1980;Sugai & Rowe, 1984). Particularly important, a recent study ) demonstrated that severely handicapped children with autism can successfully reduce a difficult behavior ( self-stimulation) using selfmanagement procedures.…”
Section: Goals and Issuesmentioning
confidence: 99%
“…As mentioned, self-management is a widely researched treatment technique that utilizes the client as an active participant in the treatment process. These procedures have not only been shown to be effective with normal populations (e.g., Drabman, Spitalnik, & O'Leary, 1973;O'Brien, Riner, & Budd, 1983;Sagotsky, Patterson, & Lepper, 1978), but have also been used successfully with persons evidencing mild to moderate mental retardation (Gardner, Cole, Berry, & Nowinski, 1983;Horner & Brigham, 1979;Shapiro & Klein, 1980;Shapiro, McGonigle, & Ollendick, 1980;Sugai & Rowe, 1984). Particularly important, a recent study ) demonstrated that severely handicapped children with autism can successfully reduce a difficult behavior ( self-stimulation) using selfmanagement procedures.…”
Section: Goals and Issuesmentioning
confidence: 99%
“…να επιλέγει και να παρέχει τους ενισχυτές). Μόνο όταν ο εκπαιδευόμενος κατανοήσει τη σχέση συνάφειας που διέπει τη συμπεριφορά του με τα επακόλουθα, τότε πλέον μπορεί να ξεκινήσει η διαδικασία της αυτοπαροχής επακόλουθων (O'Brien et al, 1983).…”
Section: αυτοπαροχή ενισχυτικών επακόλουθωνunclassified